Intelligent Manufacturing Production Line Simulation of Super Capacitor - Li He; Tengyu Li; Bin He (Journal of Robotics and Control (JRC), 2021)
With the improvement of sensing technology, the improvement of software and hardware technology and computer operation ability, the digital twin technology has been further developed with the promotion of industrial intelligence and industrial information system. Digital twin technology is gradually applied to the simulation design and optimization of complex production line. The production line of super capacitor is a kind of complex production lines, so many factors need to be considered in the design process. Therefore, the digital twin technology is used to design the production line. In this paper, the plant simulation software of Siemens company is used to simulate the super capacitor production line, so as to verify the rationality of the application of digital twin technology in the complex production line design process, and study the influence of AGV car characteristics on the production line. Simulation in virtual space can well demonstrate the actual production process. The failure and other factors in the actual production process can be replaced in the form of failure rate in the simulation environment. Data statistics and other functions can directly see the changes of various parameters in the production line, to get a better optimization scheme.